Biobanking of fresh-frozen endoscopic biopsy specimens from esophageal adenocarcinoma. Issue 8 (1st December 2016) - Stiekema, J.; Cats, A.; Boot, H.; Langers, A. M. J.; Balague Ponz, O.; van Velthuysen, M. L. F.; Braaf, L. M.; Nieuwland, M.; van Sandick, J. W.
Summary: The process of preparing endoscopic esophageal adenocarcinoma samples for next-generation DNA/RNA sequencing is poorly described. Therefore, we assessed the feasibility and pitfalls of preparing esophageal adenocarcinoma endoscopic biopsies toward DNA/RNA samples suitable for next-generation sequencing. In this prospective study, four tumor biopsy samples were collected from consecutive esophageal cancer patients during esophagogastroduodenoscopy and fresh-frozen in liquid nitrogen. DNA and RNA were isolated from samples with a tumor percentage of at least 50%. For next-generation sequencing, double-stranded DNA (dsDNA) is required and high-quality RNA preferred. The quantity dsDNA and RNA quantity and quality were assessed with the Nanodrop 2000 spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA) and Agilent 2100 Bioanalyzer (Agilent, Santa Clara, CA, USA). Biopsy samples of 69 consecutive patients with esophageal adenocarcinoma were included. In five patients (7%), the tumor percentage was less than 50% in all four biopsies. Using a protocol allowing simultaneous DNA and RNA isolation, the median dsDNA yield was 2.4 μg (range 0.1–12.0 μg) and the median RNA yield was 0.5 μg (range 0.01–2.05 μg). The median RNA integrity number of samples that were fresh-frozen within 30 minutes after sampling was 6.7 (range 4.2–8.9) compared with 2.5 (1.8–4.5) for samples that were fresh-frozen after 2 hours. The results from this study show that obtaining dsDNA and RNA for next-generation sequencing from endoscopic esophageal adenocarcinoma samples is feasible. Tumor percentage and dsDNA/RNA yield and quality emphasize the need for sampling multiple biopsies and minimizing the delay before fresh-freezing.